Top secret executive resumes - Provenzano, Steven A. (Franklin Lakes, NJ : Career Press, 2000)
This book is about: Today's executive resume; Assessing your skills; Organizing a High-Impact resume; The Pro-active executive resume; Using a title or objective; ...
Keywords: Executives; Resumes; Executives; Resumes (Employment)